Factors determining willingness to adopt Islamic leadership styles in the case of Malaysian accountants - Nurjeehan Ayub; Hanudin Amin; Fitriah Ab Rahim (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The Prophet Muhammad (P.B.U.H) is the greatest leader of all times and he is an exemplary example of the best governmental leaders that is ever witnessed by the world and even after his death, his influence is still extending, powerful and pervasive. This paper is aimed at examining the factors determining the willingness to adopt Islamic leadership styles among Malaysian accountants in which five variables which are attitude, subjective norms, perceived behavioral control, perceived vicegerency, and perceived accountability personality are examined. Partial least squares (PLS) approach is employed to test the research hypotheses. The results obtained suggest that attitudes, subjective norms, perceived behavioral control, and perceived vicegerency are important in determining the willingness to adopt Islamic leadership styles among Malaysian accountants. Limitations and potential future research are provided